Evaluation of the possible protective role of naringenin on gentamicin-induced ototoxicity: A preliminary study - AKAKIN, DİLEK (ELSEVIER IRELAND LTD, 2017)
Objectives: The purpose of this study is to evaluate the possible protective role of naringenin in gentamicin-induced ototoxicity through an audiological, biochemical and histopathological evaluation. Methods: This study was conducted on 32 adult male rats that were randomized into 4 groups(control, gentamicin, naringenin + gentamicin, and naringenin). Naringenin was given to the rats via oral gavage in a dose of 50 mg/kg/day during the 14 day study period. Gentamicin was given by the intraperitoneal route in a dose of 120 mg/kg/day. Audiological assessment was performed by the distortion product otoacoustic emission (DPOAE) and auditory brainstem response (ABR) measurements, applied to all rats at the beginning of the study, and also on day 14. Biochemical parameters were calculated on day 14 to evaluate the oxidative and antioxidative status. Their cochleae were removed and examined histopathologically, also on day 14. The cochlea of animals were evaluated with the terminal deoxynucleotidyl transferase-mediated dUTPbiotin nick end labeling (TUNEL) method for apoptosis. Results: On days 14, DPOAE values and ABR thresholds were preserved in group 3(naringenin + gentamicin) when compared with group 2(gentamicin)(p < 0.008). The total oxidant status values and oxidative stress index values were significantly higher in group 2(gentamicin) than in other groups (p < 0.008). The total antioxidant status value was significantly higher in group 3(naringenin + gentamicin) and group 4(naringenin) than in group 2(gentamicin)(p < 0.008). The number of TUNEL positive cells in both the organ of Corti and the stria vascularis were found to be statistically lower in group 3(naringenin + gentamicin) than in group 2(gentamicin)(p < 0.05). Conclusion: Our study has demonstrated that the ototoxic effect generated by gentamicin could be ameliorated with the concurrent use of naringenin. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Naringenin; Gentamicin; Ototoxicity; TUNEL; Auditory brainstem responses; Otoacoustic emission; Oxidative status; Anti-oxidative status; INDUCED NEPHROTOXICITY; INTRATYMPANIC GENTAMICIN; MENIERES-DISEASE; NITRIC-OXIDE; HAIR-CELLS; RATS; PREVENTION; ANTIOXIDANT; MODEL; INFLAMMATION